Socially Enhanced Services Computing Modern Models and Algorithms for Distributed Systems - Dustdar, Schahram; Schall, Daniel; Skopik, Florian; Juszczyk, Lukasz; Psaier, Harald (Springer eBooks., 2011)
Socially enhanced Services Computing deals with a novel and exciting new field at the intersection between Social Computing, Service-oriented Computing, Crowd Computing, and Cloud Computing. The present work presents a collection of selected papers by the editors of this volume, which they feel will help the reader in understanding this field. The approach discussed allows for a seamless integration of people into trusted dynamic compositions of Human-provided Services and Software-based services, thus empowering new interaction models and processes in massive collaboration scenarios in a Future Internet.